2011
DOI: 10.1099/jmm.0.031336-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of division I (cfiA-negative) and division II (cfiA-positive) Bacteroides fragilis strains by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is increasingly used in clinical microbiological laboratories to identify bacteria and fungi at a species level and to subtype them. The cfiA gene encoding the unique carbapenemases found in Bacteroides is restricted to division II Bacteroides fragilis strains. The aim of this study was to evaluate whether MALDI-TOF MS is suitable for differentiating B. fragilis strains which harbour the cfiA gene from those that do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 32 publications
4
76
1
4
Order By: Relevance
“…Investigators noted a good correlation of MS types with cifA types based on the evolutionary history of the species. Apparently, the cifA gene has been acquired by one lineage and has not been further spread by horizontal gene transfer (25,33). Other resistance mechanisms that rely on the activity of single resistance determinants may be amenable to the same approach.…”
Section: Innovative Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators noted a good correlation of MS types with cifA types based on the evolutionary history of the species. Apparently, the cifA gene has been acquired by one lineage and has not been further spread by horizontal gene transfer (25,33). Other resistance mechanisms that rely on the activity of single resistance determinants may be amenable to the same approach.…”
Section: Innovative Applicationsmentioning
confidence: 99%
“…In the future, MS technology in clinical microbiology will be extended to include characterization of host and microbial proteins, sugars, fatty acids, nucleic acids, and metabolites in a single clinical sample (25). This will require greater integration into laboratory workflow and further technical improvement, especially with respect to analyte detection sensitivity.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Some automated systems can provide an antimicrobial susceptibility test (AST) report after a few hours. In the case of Bacteroides fragilis, it was recently shown that the differentiation between cfiA-negative and cfiA-positive isolates (cfiA encodes a class B metallo-beta-lactamase) was possible directly from matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) profile spectra (13,20). However, such a clonal differentiation of resistant and susceptible clones cannot be expected for the majority of bacteria.…”
mentioning
confidence: 99%
“…Although MALDI-TOF MS has facilitated the identification of B. fragilis and its subsequent differentiation into division I and II strains, without a selective medium, recognition of B. fragilis in mixed growth with other bacteria remains difficult (9,13). Surveillance for drug-resistant B. fragilis strains in various patient populations also requires the availability of a selective and differential culture medium.…”
mentioning
confidence: 99%